Automation of processes of design of multifactor objects of research - Костенко, Е. М. (Scientific Progress & Innovations, 2012)
Methodology of automation of processes of design of multifactor objects of research is examined in the article. The automated stand is offered for the design of such objects of research, as technological processes, devices and systems. It allows automatizing the processes of obtaining plans by calculating the best cost and time of experiment, conducting multifactor experiments and processing their results. Speed of conducting multifactor experiments and processing their results increases thus, influence of human factor on the results of experiment is eliminated, cost expenses on their conducting are reduced.